Development of biological agents using Chrysanthemum Indicum (Asteraceae) and Alpinia Galanga (Zingiberaceae) against Coptotermes Gestroi, Coptotermes Curvignathus and Macrotermes Carbonarius / Partiban S/O Subramanian - Subramanian, Partiban (2013)

(untitled)
The antifeedant effects studies of Alpinia galanga rhizome and Chrysanthemum indicum on Coptotermes gestroi, Coptotermus curvignathus and Macrotermus carbonarius were conducted in the laboratory. Dual choice bioassays were conducted using methanolic extract and essential oil of A. galanga. Two paper discs (4.0 cm diameter) were placed in Petri dishes (9 cm diameter). One disc treated with A. galanga or C. indicum extract and another disc was treated with solvent hexane or methanol as control. Ten termites were placed in the treated petri dish. Percentage of antifeedant was determined by calculating the difference in the paper consumption of treated and control. Data was analysed statistically using ANOVA. Both A. galanga and C. indicum oil showed antifeedant effects on C. gestroi, C. curvignathus and M. carbonarius adults. 2000 ppm of A. galanga and C. indicum essential oil was considered as optimum concentration that gave maximum antifeedant effect. The essential oil composition was determined using Gas Chromatography and Gas Chromatography Mass Spectrometry (GCMS). The major compound of the essential oil of Alpinia galanga is 1,8-cineol (44.75%) whereas Germacrene D (14.07%) is the major compound of the essential of C. indicum. The antifeedant activity of A. galanga essential oil is due to 1,8-cineol. Bioassay with synthetic compound, 1,8-cineol shows 200 ppm concentration is the optimum concentration that can cause antifeedant effect on C. gestroi after 24 hours of exposure. However, for synthetic farnesene, 500 ppm concentration is the minimum concentration that can cause antifeedant effect on C. gestroi. In C. curvignathus, 500 ppm 1,8-cineol and 500 ppm farnesene is considered as minimum concentration that can cause antifeedant effect. Similarly, 500 ppm 1,8-cineol is considered as the minimum concentration that can cause antifeedant effect on M. carbonarius and 1000 ppm considered as the minimum concentration that can cause antifeedant effect on M. iii carbonarius in this study. Acute toxicity studies (ED50) shows that Macrotermes carbonarius (ED50=2512 and 1905) was more susceptible than C. gestroi and C. curvignathus to essential oils of A. galanga and C. indicum, synthetic compound (1, 8-cineol and farnesene, ED50=259 and 2455 respectively) and commercial termiticide, chlorpyrifos (ED50=174). All the three species of termites were significantly more susceptible towards the commercial termiticide, chlorpyrifos compared to the synthetic compound, 1, 8-cineol and farnesene. In the field application study on wood, 5000 ppm of 1,8-cineol and farnesene gave maximum antifeedant effect (89.47% and 67.77% respectively) on C. gestroi after 14 weeks. Alpinia galanga and C. indicum essential oils showed potential to be used as alternative control method against termite in sustainable agriculture practices. Keywords: Alpinia galanga; Essential oil; Coptotermes gestroi; Coptotermes curvignathus; Macrotermes carbonarius; 1, 8-cineol; Farnesene; Chlorpyrifos; Termite antifeedant.